From the Ethos of Housekeeping to the Doctrine of Ecology: Paradigm-shifts in the Politics of Domestic Garbage-Disposal - Moisi, Laura (Pivot: A Journal of Interdisciplinary Studies and Thought, 2015)
The aim of this article is to illuminate the political dimensions of modern waste disposal practices by comparing the representation of garbage, filth, hygiene, health and efficiency during the emergence of the modern kitchen at the beginning of the 20th century with today’s discourse of ecology, recycling and global responsibility. At issue will be mechanisms of identifying, collecting and handling trash in modern homes as well as the implied hierarchical order of decay and growth, that are set in very specific contexts of normalization and deviance. With regard to the notion of an ‘aesthetic regime’ as developed by Jacques Rancière, an assumption the paper both works with and tries to make plausible is that political matters not only emerge in the realm of deliberate action and public debate, but are fundamentally played out in the realm of sensual perception, notably through everyday ways of seeing as embedded in mundane practice and discourse.